Hydroxycarboxylic Acid Receptor 2 Is a Zika Virus Restriction Factor That Can Be Induced by Zika Virus Infection Through the IRE1-XBP1 Pathway - Ma, Xiaocao; Luo, Xin; Zhou, Shili; Huang, Yanxia; Chen, Cancan; Huang, Changbai; Shen, Li; Zhang, Ping; Liu, Chao (Frontiers in Cellular and Infection Microbiology, 2020)
Zika virus (ZIKV) is an emerging arthropod-borne virus and belongs to the Flaviviridae family. The infection of ZIKV has become the global health crisis because of its rapid spread and association with severe neurological disorders, including congenital microcephaly and Guillain-Barre Syndrome. To identify host factors contributing to ZIKV pathogenesis, transcriptomic landscape in ZIKV-infected cells was examined with mRNA microarray analysis and we observed that the expression of hydroxycarboxylic acid receptor 2 (HCAR2) could be significantly induced by ZIKV infection. By utilizing two IRE1 inhibitors and XBP1-specific shRNAs, we revealed that the up-regulation of HCAR2 expression induced by ZIKV was dependent on the IRE1-XBP1 pathway. Through the CRISPR/Cas9 system, we generated HCAR2-deficient cell clones in two cell types (human lung carcinoma epithelial A549 cell and human hepatoma Huh7.5 cell). We found that the depletion of HCAR2 significantly increased the replication level of ZIKV, including RNA levels, protein expression levels, and viral titers. In addition, our data demonstrated that the antiviral effect of HCAR2 was not involved in viral entry process and was not dependent on its antilipolytic effect on nicotinic acid/HCAR2-mediated signaling pathway. Taken together, our results indicated that HCAR2 could function as a restriction factor in control of ZIKV replication, potentially providing a novel molecular target for anti-ZIKV therapeutics.